Reconstruir la mirada experiencia en el taller de formación audiovisual en el centro juvenil de medio cerrado Lima 01 “Maranguita” - Cáceda Salas, Aldo Rafael (2020)
This professional proficiency work concisely narrates my most important experiences as a filmmaker and audiovisual producer over my past 20 years of career path. It also focuses on describing, analyzing and reflecting on my experience from my participation as a project creation manager and consultant of the Audiovisual Training Workshop at the Juvenile Center of Diagnosis and Rehabilitation of Lima, known as "Maranguita".